PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BANK BTN KANTOR CABANG KOTA MEDAN - Dinar Pratiwi Sinaga; Amirudin; Mella Yunita (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
The purpose of this research is to determine the influence of career development and motivation on employee performance at Bank BTN Medan City Branch Office. This research was conducted on Bank BTN Medan City Branch Office employees with a sample of 62 employees. The research instrument was a questionnaire with a Likert scale model. The requirements test was carried out to test normality. The data analysis technique used was the Multiple Regression technique at a significance level of a = 0.05. The results of this study indicate that career development (X1) has a significant effect on employee performance at Bank BTN Medan City Branch Office. The calculated t value is greater than the t table (2.008 ˃ 2.00172) with a significant value of 0.049. While motivation (X2) has a significant effect on employee performance. So if Bank BTN Medan City Branch Office with a calculated t value is greater than the t table (4.837 ˃ 2.00172) with a significant value of 0.000. Based on the SPSS output, it is known that the R squared value is 0.379, meaning that the variance of the performance variable can be explained by career development (X1) and motivation (X2) by 37.9 percent, while the remaining 62.1 percent is explained by other variables not included in this model. In other words, there are still other independent variables that influence employee performance.